ENHANCING MORAL INTEGRITY: ISLAMIC EDUCATION'S ROLE IN FOSTERING SUPERIOR CHARACTER WITHIN ISLAMIC BOARDING SCHOOL MANAGEMENT - M. Wahyu Hidayat; Janan, Mazkiyil (Managere: Indonesian Journal of Educational Management, 2023)
Character education plays an important role in the formation of an individual's personality with integrity. This study aims to explore the implementation of character education in Islamic Religious Education (PAI) learning in Islamic boarding schools and its impact on student character development. The research method used is qualitative research with a case study approach. This research was conducted at Lubbul Labib Islamic Boarding School located in Probolinggo Regency. The study participants consisted of PAI teachers and students involved in PAI learning at the Islamic boarding school. Data was collected through in-depth interviews, observation, and documentation analysis. The results showed that character education in PAI learning in Islamic boarding schools was carried out through various strategies and methods involving Islamic religious values as the main foundation. This research makes an important contribution to the development of character education in Islamic boarding schools and provides insight into the importance of character education in PAI learning. The implications of this study can be used as a guideline for other Islamic boarding schools in improving the effectiveness of character education in PAI learning.